Primary central nervous system marginal zone B‐cell lymphoma arising from the dural meninges: A case report and review of literature - Lopetegui‐Lia, Nerea (Clin Case Rep, 2020)
Primary central nervous system (CNS) marginal zone B‐cell lymphoma (MZBCL) arising from the dural meninges is a rare but indolent disease. This malignancy can present in various ways, hence making it difficult to diagnose. Biopsy results dictate an appropriate treatment plan, which commonly consists of a combination of surgical resection, whole brain radiotherapy and systemic therapy.